Effects of Carvedilol on the Exercise Parameters - Al-Kurashiy, Hayder M K; Abdalwahab, Iman N; Algareeb, Ali I A; Alwindy, Salahaldun B (Al-Nahrain Journal of Science, 2011)
The aim of this study is to show the effects of carvedilol on exercise parameters. Fifty four volunteers enrolled in this study, 35 males &19 females. They do exercise on bicycle ergometer, the results was non-significant effects of carvedilol on the exercise unlike other β-blocker that produce fatigue.